Bleeding canker of pears caused by Dickeya fangzhongdai: Symptoms, etiology and biology - Bin CHEN; Yan-li TIAN; Yu-qiang ZHAO; Jia-nan WANG; Zhi-gang XU; Xiang LI; Bai-shi HU (Journal of Integrative Agriculture, 2020)
Bleeding canker, a devastating disease of pear trees (Pyrus pyrifolia L.), was first reported in the 1970s in Jiangsu, China and more recently in other provinces in China. Trees infected with bleeding canker pathogen, Dickeya fangzhongdai, develop cankers on the trunks and branches, and a rust-colored mixture of bacterial ooze and tree sap could be seen all over the trunks and branches. In this study, we provided detail descriptions of the symptoms and epidemiology of bleeding canker disease. Based on pathogenic and phenotypic characterizations, we identified the causal agent of bleeding canker of pear as D. fangzhongdai. Dickeya fangzhongdai strains isolated from pear were also pathogenic on Solanum tuberosum, Brassica pekinensis, Lycopersicon esculentum, and Phalaenopsis aphrodite based on artificial inoculation, and the pathogen were more virulent on potato than that of D. solani strain. This study provides new information about this disease and bleeding canker disease of pear.